Flexibility and Adaptation of Contract Law: Comparative Study Between Indonesia's Civil Law System and Singapore's Common Law - Syafa'i, Imam; Megasari, Indah Dewi (Westscience Press, 2024)
This study aims to explore the differences in the flexibility and adaptation of contract law in Indonesia which adheres to the civil law system and Singapore which is based on common law, as well as its implications for modern business. Contract law in Indonesia is still heavily dependent on the Civil Code (KUHPerdata), which dates back to the colonial era and has not undergone significant updates. This has led to stiffness in the implementation of contracts, especially in fast-growing business sectors such as digital technology. In contrast, Singapore has adopted a common law system, which is more flexible and able to adapt to changes in the economy and international business dynamics through the use of precedents. In a business context, flexibility and legal adaptation are essential because contracts often have to adapt to new emerging needs, including changes in technology, regulations, and market conditions. This study uses a normative juridical approach with a comparative method, examining laws, court decisions, and related academic literature. The case study of business contracts between Indonesian and Singaporean companies in the technology sector is also used as a study material to provide a practical view of the effectiveness of each country's legal system in facing contemporary business challenges. The results show that Singapore excels in contract flexibility due to the use of precedents that allow for legal adjustments without the need for formal legislative changes. On the other hand, contract law in Indonesia is often unable to keep up with rapid developments due to rigid and outdated regulatory limitations. This difference has an impact on the speed and efficiency of contract dispute resolution in both countries, with Singapore being able to resolve disputes more quickly through a more responsive system. This study concludes that to increase competitiveness in the global economy, Indonesia needs to reform the Civil Code to be more flexible and adaptive like the one implemented in Singapore. These recommendations are important to ensure that Indonesia can create a more competitive business environment and support innovation, especially in the ever-evolving digital era.